DESCRIPTION OF HIV (HUMAN IMMUNODEFICIENCY VIRUS) IN CATIN (PROSPECTIVE BRIDAL) IN GORONTALO CITY - Bau, Devriyanti Oskar (Jurnal Ilmiah dr. Aloei Saboe, 2022)
HIV (Human Immunodeficiency Virus) is a viral infection that attacks the human immune system. To detect HIV early, an HIV screening examination is carried out on the prospective bride and groom recommended at the health center using the rapid test method to detect early medical history of the prospective bride and groom. If a disease or abnormality is found, then medical action can be taken immediately. If the disease or disorder is not resolved, efforts will be made to ensure that the bride and groom make efforts to prevent the problem from getting worse or spreading to her partner. This study aims to determine the results of HIV examination on catin (bride and groom) and to determine the factors of HIV transmission, namely through blood transfusions, family history of HIV, ever taking drugs, employment, and education of the prospective bride and groom. As well as knowing the characteristics of the prospective bride based on age and gender. This type of research is a descriptive study with a quantitative approach, and HIV testing using the rapid test method. This research technique uses the Cluster Random Sampling technique, which is an area sampling technique used to determine the sample if the object to be studied or the data source is very broad. The results of HIV examination showed that the catin (bride and groom) was not infected with HIV (non-reactive) with a percentage of 100%.